Policy Implementation Model Agency Accounting System (SAI) Based On The Technology Acceptance Model (TAM) at The South Sumatra Regional Police - Bekti, Sugeng Prasetyo; Sobri, Kiagus Muhammad; Sriati, Sriati; Putra, Raniasa (Journal Public Policy, 2025)
This research discusses the Performance Evaluation of Implementation of Institutional Accounting System (SAI) Policies with Approach Technology Acceptance Model (TAM) at the South Sumatra Regional Police. The aim of this research is: to evaluate the performance of the implementation of agency accounting system (SAI) policies using the approach Technology Acceptance Model (TAM) at the South Sumatra Regional Police. factors that support and inhibit the Implementation of the Agency Accounting System (SAI) Policy in the South Sumatra Regional Police as well as the optimal model of Implementation of the Agency Accounting System (SAI) Policy for the South Sumatra Regional Police. The research method uses qualitative research with data collection techniques indepth interview, observation, and documentation to analyze the Performance Evaluation of Implementation of Agency Accounting System (SAI) Policies with Approach Technology Acceptance Model (TAM) at the South Sumatra Regional Police.The research results show an evaluation of the performance of implementing agency accounting system (SAI) policies using the approach Technology Acceptance Model (TAM) at the South Sumatra Regional Police is quite good. However, there are still problems. Policy content includes: Policy Complexity, Unclear Goals and Targets, Incompatibility with Organizational Needs, Difficulty in Technical Understanding, Non-conformity with Regulations and Standards, and Unclear Implementation Procedures. Obstacles in the implementation context include: limited resources, system integration difficulties, changes in organizational culture, lack of skills and knowledge, information security issues, regulatory compliance, and difficulties in determining clear success criteria and measuring the impact of SAI implementation can be a challenge. Without proper measurement, it is difficult to evaluate whether implementation has achieved organizational goals Keywords: Policy Implementation, Agency Accounting System (SAI), Technology Acceptance Model (TAM)